2008
DOI: 10.1097/prs.0b013e31816b1458
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Abdominal Donor-Site Morbidity in Free Flap Breast Reconstruction

Abstract: Donor-site complications are not uncommon, but paying careful attention to patient comorbidities when selecting an operative approach (bilateral versus unilateral, free TRAM versus DIEP, and so on) can minimize postoperative abdominal complications. Furthermore, the results corroborate the recent literature suggesting there is little functional difference in patients receiving muscle-sparing free TRAM versus DIEP reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 26 publications
7
110
0
Order By: Relevance
“…In the current study, the overall incidence of donor-site complications was 25.8 percent. Increasing body mass index was associated with increased overall donorsite complications coinciding with similar trends observed previously among obese patients following TRAM 11,18,29 or DIEP flap 30 reconstruction. On close examination, however, differences in overall donor-site complications based on body mass index in the current series can be attributed to delayed wound healing, as other individual complications were similar across all body mass index groups.…”
Section: Donor-site Complicationssupporting
confidence: 86%
“…In the current study, the overall incidence of donor-site complications was 25.8 percent. Increasing body mass index was associated with increased overall donorsite complications coinciding with similar trends observed previously among obese patients following TRAM 11,18,29 or DIEP flap 30 reconstruction. On close examination, however, differences in overall donor-site complications based on body mass index in the current series can be attributed to delayed wound healing, as other individual complications were similar across all body mass index groups.…”
Section: Donor-site Complicationssupporting
confidence: 86%
“…[33][34][35][36][37][38][39] Among breast reconstruction patients, obesity has been shown to increase complication rates in both implant-based and autologous immediate breast reconstruction. 1,2,4,[6][7][8]14,[40][41][42][43][44] The overall complication rate in our obese patients undergoing oncoplastic breast reconstruction and immediate breast reconstruction was comparable to other studies 41,45 ; however, no single-center studies exist with sufficiently powered logistic regression analysis to evaluate specific predictive factors between oncoplastic breast reconstruction and immediate breast reconstruction complications among the obese. In a 2010 study, Losken et al showed that rates of complications and revision operations were significantly higher for patients following skin-sparing mastectomy and immediate breast reconstruction than for women with macromastia who underwent oncoplastic breast reconstruction.…”
Section: Discussionmentioning
confidence: 51%
“…Autologous tissue breast reconstruction offers the greatest patient satisfaction 3 , so its use is gaining popularity worldwide 4 with the deep inferior epigastric perforator (DIEP) flap evolving as the ideal choice for autologous reconstruction in suitable women. Breast reconstruction with DIEP flap(s) is associated with lower risks of adverse outcomes 5 , favourable donor site morbidity [6][7][8][9] , improved quality of life 10 , shorter hospital stay 11,12 , reduced postoperative pain [13][14][15] and superior cosmetic results…”
Section: Introductionmentioning
confidence: 99%